Atezolizumab plus platinum-based chemotherapy as first-line therapy for metastatic urothelial cancer: A cost-effectiveness analysis - Liu, Xiaoyan; Lang, Yitian; Chai, Qingqing; Lin, Yan; Liao, Yahui; Zhu, Yizhun (Frontiers in Pharmacology, 2022)
Purpose: According to the IMvigor130 trial, adding atezolizumab to platinum-based chemotherapy was effective in treatment of metastatic Urothelial Cancer (mUC). Based on the perspective of the United States and China, the current study evaluated cost-effectiveness of atezolizumab plus chemotherapy for mUC patients in the first-line setting. Methods: A partitioned survival model was adopted for mUC patients. The survival data were derived from IMvigor130 trial. Direct costs values were collected from the Centers for Medicare and Medicaid Services (CMS), Chinese Drug Bidding Database and published literatures. The utility and toxicity data were gathered from related researches and IMvigor130 trial. The incremental cost-utility ratios (ICURs) and incremental cost-effectiveness ratios (ICERs) were calculated and analyzed. Scenarios analyses and sensitivity analyses were performed to observe the outputs and uncertainties. Results: The base-case analysis showed that the ICUR of atezolizumab plus chemotherapy versus chemotherapy in American and Chinese setting is 737,371 /QALY and 385,384 /QALY, respectively. One-way sensitivity analyses showed that the ICUR ranged from 555,372/QALY to 828,205/QALY for the United States. And the range was from 303,099/QALY to 433,849/QALY in the Chinese setting. Probabilistic sensitivity analysis showed the likelihood that atezolizumab plus chemotherapy become preferred strategy was a little low even if the price reduction strategy was applied. Conclusion: Adding atezolizumab to chemotherapy improved survival time, but it is not a cost-saving option compared to chemotherapy for metastatic urothelial cancer patients in the American and Chinese setting.